Solid State Electrolytes: Nonuniform Ionic and Electronic Transport of Ceramic and Polymer/Ceramic Hybrid Electrolyte by Nanometer‐Scale Operando Imaging for Solid‐State Battery (Adv. Energy Mater. 21/2020). Issue 21 (2nd June 2020) - Jiang, Chun‐Sheng; Dunlap, Nathan; Li, Yejing; Guthrey, Harvey; Liu, Ping; Lee, Se‐Hee; Al‐Jassim, Mowafak M.
Abstract : In article number 2000219 Chun‐Sheng Jiang and co‐workers find highly inhomogeneous ionic and electronic transport in ceramic and polymer/ceramic hybrid solid state electrolytes by developing an atomic force microscopy‐based half‐cell setup, and using a logarithm‐scale amplifier with a wide current range in mA‐fA. This nonuniform ionic current originates from highly crystalline orientation‐dependent kinetic barriers and represents a new factor for induction of Li dendrite formation and growth that should be mitigated.